Process characterization and Design Space definition. Issue 5 (September 2016) - Hakemeyer, Christian; McKnight, Nathan; St. John, Rick; Meier, Steven; Trexler-Schmidt, Melody; Kelley, Brian; Zettl, Frank; Puskeiler, Robert; Kleinjans, Annika; Lim, Fred; Wurth, Christine
Abstract: Quality by design (QbD) is a global regulatory initiative with the goal of enhancing pharmaceutical development through the proactive design of pharmaceutical manufacturing process and controls to consistently deliver the intended performance of the product. The principles of pharmaceutical development relevant to QbD are described in the ICH guidance documents (ICHQ8-11). An integrated set of risk assessments and their related elements developed at Roche/Genentech were designed to provide an overview of product and process knowledge for the production of a recombinant monoclonal antibody (MAb). This chapter describes the tools used for the characterization and validation of MAb manufacturing process under the QbD paradigm. This comprises risk assessments for the identification of potential Critical Process Parameters (pCPPs), statistically designed experimental studies as well as studies assessing the linkage of the unit operations. Outcome of the studies is the classification of process parameters according to their criticality and the definition of appropriate acceptable ranges of operation. The process and product knowledge gained in these studies can lead to the approval of a Design Space. Additionally, the information gained in these studies are used to define the 'impact' which the manufacturing process can have on the variability of the CQAs, which is used to define the testing and monitoring strategy.